Discovery of 1 Hz Range Modulation of Isolated Proton Aurora at Subauroral Latitudes. Issue 3 (5th February 2018) - Ozaki, M.; Shiokawa, K.; Miyoshi, Y.; Kataoka, R.; Connors, M.; Inoue, T.; Yagitani, S.; Ebihara, Y.; Jun, C.‐W.; Nomura, R.; Sakaguchi, K.; Otsuka, Y.; et al.
Abstract: Isolated proton aurora (IPA) is a manifestation of the wave‐particle interaction visible at subauroral latitudes, with activity on many timescales. We herein present the first observational evidence of rapid luminous modulation of IPA correlated with simultaneously observed Pc1 waves observed on the ground, which are equivalent to the electromagnetic ion cyclotron (EMIC) waves in the magnetosphere. The fastest luminous modulation of IPA was observed in the 1 Hz frequency range, which was twice the frequency of the related Pc1 waves. The time lag between variations of Pc1 wave power and the IPA luminosity suggests that the source regions of IPA are distributed near the magnetic equator, suggesting an EMIC wave‐energetic (a few tens of keV) proton or relativistic (MeV or sub‐MeV) electron interaction. The generation mechanism of this 1 Hz luminous modulation remains an open issue, but this study supports the importance of nonlinear pitch angle scattering via wave‐particle interactions. Plain Language Summary: This study presents the discovery of a direct link between isolated proton aurora and natural electromagnetic waves known as electromagnetic ion cyclotron (EMIC) waves detected as Pc1 geomagnetic pulsations on the ground. For the first time, the fastest expected variations are detected through fast modulations of isolated proton aurora. The isolated proton aurora comes from the Earth's radiation belts, driven by plasma waves via wave‐particle interaction. Theoretical studies have shown that the isolated proton aurora is generated by resonant interaction with EMIC waves. Our finding gives a clear observational evidence of this by using cutting edge observations, related to this essential physical process for energy transport in plasmas. Key Points: A theoretically expected 1 Hz luminous modulation of proton aurora was detected The 1 Hz luminous modulation showed a high correlation with Pc1 wave power The inferred IPA source regions for the 1 Hz modulation were distributed around the magnetic equator